2014
DOI: 10.1128/jcm.01573-14
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Second Diagnostic Window for Human Immunodeficiency Virus Type 1 in a Fourth-Generation Immunoassay: Are Alternative Testing Strategies Required?

Abstract: dDiagnosis of acute HIV is done by patient history and examination and testing of RNA, proviral DNA, and serology using fourthgeneration antigen/antibody detection assays. We describe an HIV-1 primary infection with a second diagnostic window of 18 to 34 days on a fourth-generation immunoassay, which would have been missed using some current algorithms. Caution must be exercised when fourth-generation HIV-1 immunoassays are interpreted in isolation, and additional testing should be considered depending on pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We found that the Abbott i2000 performed significantly better than the ELISA on HBV and HCV screening; however, for anti‐TP and anti‐HIV, the ELISA remained the preferred method. The presence of a second diagnostic window for fourth‐generation HIV assays has been reported . During this period, the reduction in the p24 antigen and antigen/antibody complexes may affect the sensitivity of these assays, and many acute HIV infections have been missed using fourth‐generation assays.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the Abbott i2000 performed significantly better than the ELISA on HBV and HCV screening; however, for anti‐TP and anti‐HIV, the ELISA remained the preferred method. The presence of a second diagnostic window for fourth‐generation HIV assays has been reported . During this period, the reduction in the p24 antigen and antigen/antibody complexes may affect the sensitivity of these assays, and many acute HIV infections have been missed using fourth‐generation assays.…”
Section: Discussionmentioning
confidence: 99%
“…(This situation may occur either very soon after the eclipse period has ended or in a rare, second window period after p24 has cleared but before IgM has become detectable. 30 )…”
Section: Summary and Recommendations For Specific Situationsmentioning
confidence: 99%
“…33 Immunoassays for HIV-1 and HIV-2 antibodies are integral components of the current generations of HIV diagnostic assays. 33 Immunoassays for HIV-1 and HIV-2 antibodies are integral components of the current generations of HIV diagnostic assays.…”
Section: Selection Of Hiv Gp41 As a Model Systemmentioning
confidence: 99%
“…Selection of HIV gp41 as a model system Indirect immunoassays are useful in the diagnosis of infections from HIV because the production of HIV-specic antibodies is an important biomarker of seroconversion. 33 Immunoassays for HIV-1 and HIV-2 antibodies are integral components of the current generations of HIV diagnostic assays. 34 Assays for antibodies to gp41, a subunit of the HIV envelope protein, 35 are of particular interest in diagnostic assays because they: (i) can be used broadly for subclasses of HIV-1, 36 (ii) persist indenitely aer seroconversion, 33 and (iii) are passively transmitted to newborns from infected mothers as mechanism for protection.…”
Section: Materials and Regentsmentioning
confidence: 99%